Language of e-commerce: pragmatic strategies in Indonesian online marketplace advertisements - Fitriya Dessi Wulandari (Indonesian Journal of Language and Economic Discourse, 2026)
Background: The expansion of Indonesian e-commerce platforms such as Shopee, Tokopedia, Lazada, and TikTok Shop demonstrates how digital marketplaces rely heavily on persuasive language and multimodal strategies. Objective: The purpose of this study is to analyze the pragmatic strategies, speech acts, and multimodal tactics that characterize Indonesian online marketplace advertisements. Method: Using a qualitative descriptive design, the research employed Levinson’s pragmatic analysis, Searle’s speech act theory, and Kress and van Leeuwen’s multimodal discourse framework to examine a corpus of product titles, promotional captions, buyer–seller chats, and digital banners collected over three months. Results: The results reveal three major findings: first, pragmatic persuasion is dominated by urgency, scarcity, and politeness markers such as kinship terms and emojis; second, buyer–seller interactions are structured through assertives, commissives, and softened directives that balance persuasion with relational intimacy; and third, multimodal advertisements employ visual salience, color symbolism, and culturally resonant icons (e.g., Ramadan motifs) to reinforce linguistic persuasion. These findings suggest that Indonesian e-commerce communication combines global persuasive practices with local cultural adaptations. Implication: The implication of the study is that pragmatic and multimodal analyses can enrich understanding of digital persuasion, offering insights for both linguistic scholarship and practical digital marketing strategies. Novelty: The novelty of this study is to show the ways Indonesian e-commerce discourse integrates pragmatic persuasion and multimodal design with culturally embedded cues to optimize both transactional effectiveness and relational engagement in digital marketplaces.